PROGRAM PENGEMBANGAN PENDIDIKAN DALAM RANGKA MEMANDIRIKAN ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH LUAR BIASA DHARMA BHAKTI PIYUNGAN BANTUL TAHUN 2014 (JURNAL ILMIAH TUT WURI HANDAYANI, 2015)
This research aims to describe the development of educational programs in order to make independent of disable studentsin terms of planning, implementation, monitoring and evaluation of programs in Special Education of Dharma Bhakti Piyungan Bantul whichhas students with different types of disability which of course in the development programs, there are in contrast to regular school.This study used a qualitative approach. The sources of data were derived from sources or informants which include head of school, vice-head of school, teachers, staff, parents, school committees, as well as documents relating to the implementation of education development program. The data collection techniques use observation, interviews, and document scrutiny. For the validity test of data, it was done by extending research, triangulation of data, and auditing or verification of data.The research results show that the planning, implementation, monitoring and evaluation of educational development programs in order make independent of disable studentshas alreadyaccordance with 8 National Standard of Education (SNP). Skills lesson that are taught in school were a program to make independent of disable studentshas already met the school's vision. Theschool implementing the educational development program in order make independent of disable students had a Second Level Curriculum (KTSP), enough instructional media, the use of the method according to the needs of students, evaluation of learning processes in accordance with the guidelines of the department of education, and supported by adequate infrastructure, human resources and the participation of the school committee. The problems that occursare the less awareness of child's condition by some parents, the child's mood up and down, less specialized skill instructors and less information technology media. To solve the problems by home visit coaching, propose specialized skill instructors to the Yogyakarta Department of Education and propose E - Learning support.